(untitled) - Foster, Helen (London, 2004)
Modern living can be toxic to the human body--but these 14 tailor-made plans help combat the unhealthy effects of bad air, bad food, and bad habits. There are natural, easy-to-follow solutions for quitting smoking, increasing energy levels, reducing stress, busting the sugar habit, losing weight, and more. There's even a pre-party plan to help minimize the unpleasant side effects of occasional overindulging, and one to handle a hangover. With simple and delicious recipes, thoroughly illustrated exercises, instructions for massage and other alternative therapies, and plenty of lifestyle tips, this guide has all the tools you need to look and feel your best.
Keywords: Detoxification (Health)